Integration or separation? : a strategy for racial equality - Brooks, Roy L. (Roy Lavon), 1950- (Harvard University Press, 1996)
Roy L. Brooks, a distinguished professor of law and a writer on matters of race and civil rights, says with frank clarity what few will admit - integration hasn't worked and possibly never will. Equally, he casts doubt on the solution that many African Americans and mainstream whites have advocated: total separation of the races. This book presents Brooks's strategy for a middle way between the increasingly unworkable extremes of integration and separation.